Impact of 'fund of funds' and other initiatives in building entrepreneurial economy of emerging India: a comparison with China. (2018) - Habeeb, Safoora; Ahmad, Naseeb
Entrepreneurship is increasingly recognised as double edged sword that provides self-employment and creation of employment for others. Moreover, entrepreneurial Startups are considered as the next great economic force that Indian needs today. Though, the country is seen as the youngest 'Startup Nation' in the world, the survival rate of startup is miserably low. Access to finance is one of the serious problems in the way of creation and sustaining business enterprises. Government of India has recognised this need and released corpus 'fund of funds' (FoF) 10, 000 crore in June 2016, which is in line with Start Up India Action Plan. This huge corpus is expected to generate employment for 18, 00, 000 persons on full deployment. This paper is an attempt to gauge impact of such initiatives by government of India taken since 2014 specifically, to build entrepreneurial economy. Also a comparison of two emerging economies - India and China is done in the same context. Data from global entrepreneurship monitor - adult population survey (APS) and national expert survey (NES) is taken and analysed.